PENGARUH DEBT TO EQUITY RATIO BEFORE (DERB) TERHADAP TOTAL ASSET TURN-OVER (TATO) DAN RETURN ON ASSET (ROA) PADA PERUSAHAAN PERTAMBANGAN BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013 - 2018 - Mohamad Nuhnaradita Saleh; Saladin Ghalib; Suyatno Suyatno (JURNAL BISNIS DAN PEMBANGUNAN, 2021)
Coal mining companies require large investments to carry out their operational activities. This large investment must be accompanied by a solvable capital structure policy. A solvable capital structure supports the company in carrying out efficient asset turnover activities and obtaining ever-growing profitability.This study aims to analyze the causality relationship of Debt to Equity Ratio Before to Total Asset Turn-Over, and Return On Asset. This research is an explanatory study of causality with a quantitative approach. This study considers the principle of going concern and agency theory in which in making sustainable financial decisions from year to year there can be differences in interests between the main stakeholders internally. This study involved data from nine coal companies listed on the Indonesia Stock Exchange from 2013 to 2018 which were selected by purposive sampling with the consideration of the availability of data on the variables studied.The results of this study indicate that the debt to equity ratio before directly has a significant negative effect on total asset turnover, but it has no significant effect on return on assets when controlled by total asset turnover. Total asset turnover has a significant positive effect on return on assets, it has a significant fully positive mediation effect on the debt to equity ratio before.In further research, expected to include other variables as independent variables, such as asset structure, include the fractional elements of total asset turnover, for example, current asset turnover and fixed asset management.Keywords: Debt to equity ratio before, total asset turnover, return on asset